Pengaruh Displin Kerja Dan Kepemimpinan Terhadap Kinerja Karyawan Dengan Motivasi Sebagai Variabel Intervening PT XYZ - Uswatul Fitroh; Ery Teguh Prasetyo; Dody Kurniawan (Pusat Riset dan Inovasi Nasional, 2024)
Human resources are the most important capital and wealth in every human activity, meaning that a company cannot function properly without human resources. Employees have a role as planners, implementers and supervisors who always play an active role in realizing company goals. The success of a company greatly influences the performance of its employees, because employee performance is a very important starting point for the success of the company. This research aims to determine the effect of work discipline and leadership on employee performance with work motivation as an intervening variable at PT. XYZ This research design uses a quantitative research design. The population and sample size in this study were all 68 employees of PT XYZ. The data source used is primary data in the form of a questionnaire. The measurement scale used is the Likert scale. The data analysis technique used is Partical Least Square (PLS) with SmartPLS 3.2.9 software. The research results show that; work discipline, leadership, and motivation have a positive and significant effect on performance; work discipline and leadership have a positive and significant effect on motivation; and work discipline and leadership have a positive and significant influence on performance which mediates motivation.